Mycenaean and Egyptian faience beads discovered in southern Poland. (December 2019) - Purowski, Tomasz; Syta, Olga; Wagner, Barbara
Highlights: Archaeometric study of Bronze Age (c. 1600–1100 BCE) faience from Poland. Four of the beads were examined with LA-ICP-MS and one with EPMA methodology. All the analyzed beads from Poland were made in the Eastern Mediterranean. Abstract: Four faience beads discovered in southern Poland, in graves dated to roughly 1600–1100 BCE, have been the object of an archaeometric study, four with the LA-ICP-MS method and one additionally with the EPMA method. Two beads have good formal parallels from territories associated with Mycenaean culture. The material of which they were made combines features of the previously distinguished groups A and B of Mycenaean faience. The faience discovered in Poland ties it in with faiences of group A by the use of soda-rich plant ashes as a fluxing agent, whereas a similar cobalt ore colorant links it to group B. The other two beads were made most probably in Egypt, considering the use of a similar alkali raw material (halophyte plant ash) and an alum (source of cobalt) as colorant in one case. The beads must have reached the territory of Poland from the Eastern Mediterranean most probably through Italy and up the so-called Amber Road.